KUALITAS PELAYANAN PUBLIK DALAM BIDANG ADMINISTRASI KEPENDUDUKAN (Studi Pelayanan KTP-el dan KK di Kantor Kecamatan Wringinanom Kabupaten Gresik) - Inthania Rachmad Wardani; Sri Umiyati; Deasy Arieffiani (Faculty of Social and Political Science, 2020)
The study aims to analyze the quality of public service in the population administration of electronic identity card and the family card in Wringinanom district office, Gresik. Public service is the effort of institution in providing assistance for community to achieve certain goals according to the community needs. In this case, service quality is often used to know how institution performance provides public services. In term of service quality, it can reflect the performance in implementing the duty and function. Furthermore, Wringinanom district is the provider of public service in population administration, such as the service in electronic identity card and the family card. However, several problems have been found in the quality of population administration services in Wringinanom district. The study uses the variable of service quality in qualitative descriptive research method. The analysis technique applies four methods, namely data collection, reduction, presentation and conclusion. Moreover, the result indicates the quality of population administration service does not have good quality, especially in electronic identity card and the family card in Wringinanom district. It is proven from several indicators that have not been fulfilled. The first indicator is physical evidence dimension that has lack of comfortable public place. Whereas, the second indicator is reliability dimension that can be seen from the uncertain service standard. The last is empathy dimension in which the service still needs an improvement.